DAMPAK PEMILIHAN KEPALA DESA 2021 TERHADAP RELASI KEKELUARGAAN DI DESA TANDUNG KECAMATAN SABBANG - Lestari, Wilda (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2024)
This research discusses the impact of the 2021 Village Head election on family relations in Tandung Village, Sabbang District. This study aims to determine the process of selecting the Village Head in Tandung Village, the impact arising from the election of the Village Head on Family Relations and the mechanism for resolving the village head election problem that occurred in Tandung Village based on Islamic Law. The type of research used is field research (field research). The research was carried out in a systematic, orderly and in-depth manner by raising data or facts in the field using a qualitative descriptive method by collecting data that was compiled, explained, presented and then concluded, this method was used in research to examine the condition of the object nature, in which the researcher is the key instrument. The results of the study show that the impact of the 2021 Village Head election on family relations in Tandung Village has resulted in the estrangement of family relationships that have been well established so far. The Village Head election system which is carried out directly in Tandung Village does not only have an impact on family relationships but has an impact on harmony, solidarity in society and even has an impact on daily activities. The basic principle of conflict resolution in Islamic Law always begins with negotiation efforts using either mediation or deliberation by gathering perceptions or facts of events that occurred so that they are summarized and decided together. Keywords: Impact, Village Head Election and Family Relations